Implantable Device to Monitor Cardiac Activity with Sternal Wires. Issue 12 (24th August 2014) - GANAPATHY, ANAND; PALMER, AARON; BURRER, ANGIE; BERSI, MATTHEW; GARZA, JAVIER; RAZAVI, MEHDI
<x xml:space="preserve">Abstract</x> Background Sternal wires are used to close the thoracic cavity and facilitate healing after median sternotomy (MS). We invented an implantable device that uses these wires as sensors to monitor cardiac electrical activity and tested its utility in collecting electrocardiography (ECG) data in vivo. Methods The wafer‐thin silicone device has grooves with embedded metal contacts that secure the sternal wires and connect them to an ECG sensor. We used radiofrequency telemetry to communicate with the implanted device, which was evaluated in three acute swine studies and one chronic‐survival swine study. The device was implanted via MS in two acute studies and left thoracotomy in the other. In two acute studies, ECG data were collected with the pigs in four different positions for 2 minutes each; in the third study, we induced ischemia and collected ECG data. For the chronic study, we implanted the device via a left thoracotomy and obtained ECG data weekly until euthanasia on day 27. After each study, the sternum and device were removed and examined. Results The ECG tracings showed distinct P, QRS, and T waveforms with minimal positional or temporal variability. Our device captured signal changes during ischemia before the external control did. In the chronic study, necropsy showed appropriate healing, fibrous encapsulation, and no infection or adverse reactions. Conclusions These initial results showed that our novel device can use sternal wires as electrodes in vivo to monitor cardiac electrical activity and safely capture physiologic signals after surgical placement.